Numerical Simulations of Hydrodynamics of Nematic Liquid Crystals: Effects of Kinematic Transports (Communications in Computational Physics, 2011)
In this paper, we investigate the effects of kinematic transports on the nematicliquid crystal system numerically and theoretically. The model we used is a "1+2" elastic continuum model simplified from the Ericksen-Leslie system. The numericalexperiments are carried out by using a Legendre-Galerkin spectral methodwhich can preserve the energy law in the discrete form. Based on this highly accuratenumerical approach we find some interesting and important relationships betweenthe kinematic transports and the characteristics of the flow. We make some analysisto explain these results. Several significant scaling properties are also verified by oursimulations.